Building Tax Awareness From an Early Age Through Tax Literacy Education for SMA/SMK Students in Magelang - Ghina Fitri Ariesta Susilo; Agustina Prativi Nugraheni; Wildan Yudhanto; Alex Johanes Simamora; Ediet Leo Elvandy; Siti Rokhaniyah (STMIK Royal, 2026)
Abstract: Tax literacy among Indonesian youth remains relatively low and has not yet become an integral component of formal learning at the senior and vocational high school levels. National data indicate that financial literacy stands at 49.68%, while specific understanding of taxation among young people is reported to be lower than that of the productive-age population. In addition, tax return compliance among individuals under 25 years old remains limited, reflecting weak early tax awareness and tax morale. In Magelang, high school students as future taxpayers generally lack access to contextual and practice-oriented tax education. This community engagement program aims to enhance tax literacy, awareness, and basic understanding of taxation among senior and vocational high school students through a structured and participatory educational approach. The methods included interactive lectures, contextual discussions, daily tax case studies, and simple tax calculation simulations, supported by pre- and post-tests to measure learning outcomes. The results demonstrate a significant improvement in students’ tax literacy scores and attitudes toward future compliance. The program also produced a tax literacy module and initiated student tax awareness groups in partner schools. Early tax education is therefore effective in strengthening youth tax morale and supporting sustainable national development. Keywords: community engagement; magelang; tax awareness; tax literacy; youth education Abstrak: Literasi pajak di kalangan generasi muda Indonesia masih tergolong rendah dan belum menjadi bagian utama dalam pembelajaran formal di tingkat SMA/SMK. Data nasional menunjukkan tingkat literasi keuangan sebesar 49,68%, sementara pemahaman spesifik mengenai perpajakan pada kelompok usia muda lebih rendah dibandingkan kelompok usia produktif. Selain itu, tingkat kepatuhan pelaporan SPT pada wajib pajak berusia di bawah 25 tahun masih terbatas, yang mencerminkan lemahnya kesadaran dan moral pajak sejak dini. Di wilayah Magelang, siswa SMA/SMK sebagai calon wajib pajak masa depan umumnya belum memperoleh edukasi pajak yang kontekstual dan berbasis praktik. Program pengabdian kepada masyarakat ini bertujuan meningkatkan literasi, kesadaran, dan pemahaman dasar perpajakan melalui pendekatan edukasi yang terstruktur dan partisipatif. Metode yang digunakan meliputi ceramah interaktif, diskusi kontekstual, studi kasus perpajakan sehari-hari, serta simulasi perhitungan pajak sederhana yang didukung pre-test dan post-test. Hasil kegiatan menunjukkan peningkatan signifikan skor literasi pajak dan sikap kepatuhan siswa. Program ini juga menghasilkan modul literasi pajak dan pembentukan kelompok siswa sadar pajak di sekolah mitra. Edukasi pajak sejak dini terbukti efektif dalam memperkuat moral pajak generasi muda dan mendukung pembangunan nasional berkelanjutan. Kata kunci: edukasi generasi muda; kesadaran pajak; literasi pajak; magelang; pengabdian kepada masyarakat